Case report: Surgical resection of a retro-hepatic leiomyosarcoma involving atrial reconstruction, cardiopulmonary bypass, ex vivo tumor resection, and liver re-implantation - Sharma, Neel K.; Okakpu, Uchenna; Murthy, Jeevan; Wei, Lawrence M.; Lopez-Solis, Roberto; Schmidt, Carl; Badhwar, Vinay; Marsh, J. Wallis (Frontiers in Surgery, 2022)
Vascular Leiomyosarcomas (vLMS) are rare and extremely malignant tumors that present a complex surgical and logistical problem that often necessitates intricate planning, coordination and execution involving multiple subspecialties. LMS involving the inferior vena cava (IVC) is a clinically rare entity that accounts for only about 0.5% of all adult soft tissue sarcomas. The role of vascular reconstruction of the IVC is variable—with options ranging from primary repair, ligation, or reconstruction—and dictated by the level and extent of the tumor. Surgical resection with negative margins remains the treatment of choice due to the lack of efficacy of adjuvant therapies. Importantly, liver explantation offers a chance for complete surgical resection and reconstruction. Here, we present a case of retro-hepatic cava leiomyosarcoma (LMS) with liver explantation, ex-vivo tumor excision, liver re-implantation and cava reconstruction under cardiopulmonary bypass (CPB). To our knowledge, this is the first reported case in which the hepatic veins were anastomosed directly to the right atrium while also replacing the native vena cava with a separate graft.